The Hβ line dip shift measurements in wide range of plasma electron density. (January 2019) - Savić, Igor; Mijatović, Zoran; Gajo, Teodora; Gavanski, Lazar; Djurović, Stevica
Highlights: Dip shift of hydrogen H β line was measured using three plasma sources. Plasma electron density covered in this work is ( 0.17 − 6.56 ) × 1023 m − 3 . Measured dip shift shows nonlinear dependence on plasma density due to line asymmetry. Abstract: In this paper, we present experimental shift results of the dip of the Balmer Hβ line emitted from three plasma sources. The use of different sources enabled the measurements to be carried out under a wide range of plasma conditions. The electron density was in the range of (0.17–6.56) × 10 23  m −3 and electron temperature in the range of 10, 100–33, 000 K. For higher electron densities, the measured dip shift shows a nonlinear dependence on the electron density. It is shown that this nonlinearity is the consequence of the asymmetry of the Hβ line. The correlation between the measured dip shift and Hβ line halfwidths shows that the dip shift can be used for plasma electron density determination. This can be useful in cases when the Hβ spectrum cannot be fully covered by the spectral apparatus.